Adherence to the mechanical ventilation-associated pneumonia prevention bundle in neonatal and pediatric ICU (Research, Society and Development, 2023)
Ventilator-associated pneumonia (VAP) in neonatal (NEO ICU) and pediatric (PED ICU) intensive care units represents one of the most common problems related to the use of invasive devices. There are a series of measures (bundles) that can contribute to reducing VAP rates. The objective was to evaluate professionals' adherence to the bundle after an educational intervention with the team. Regarding the methodology, it was an intervention study, using data from 31 patients admitted to the NEO ICU and PED undergoing invasive mechanical ventilation (IMV) from 2021 to 2022. VAP prevention measures were verified before and after an intervention educational session with the multidisciplinary team (comparison of 150 pre-intervention observations and another 150 post-intervention observations). The results found were as follows: pre-intervention adherence rates to the items headboard between 30 and 45º, circuit without dirt, circuit without condensation, oral hygiene and physiotherapy were 79.3%, 86%, 74.7%, 6 .7% and 96%, respectively. After the intervention, the same values for the same items were: 96.7% (p